2010
DOI: 10.1038/ni.1944
|View full text |Cite
|
Sign up to set email alerts
|

IL-37 is a fundamental inhibitor of innate immunity

Abstract: The function of interleukin 37 (formerly IL-1 family member 7) remains elusive. Expression of IL-37 in macrophages or epithelial cells imparted near complete suppression of pro-inflammatory cytokines, whereas the abundance of these cytokines increased with silencing of endogenous IL-37 in human blood cells. Anti-inflammatory cytokines remained unchanged under similar conditions. IL-37-transgenic mice were protected from lipopolysaccharide-induced shock, exhibiting markedly improved lung and kidney function and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
1,248
2
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 765 publications
(1,359 citation statements)
references
References 45 publications
67
1,248
2
11
Order By: Relevance
“…Some endogenous molecules inhibit IL1 and TNF and also attenuate spontaneous NREMS including IL-4, IL-10, IL-13, 3 corticotrophin releasing hormone, 35 IL1-receptor antagonist, 4 and others (see Figure 1). We have recently found that transgenic mice with the ability to express human IL-37b, a suppressor of multiple pro-somnogenic cytokines 36 sleep less after sleep deprivation than under baseline conditions. 37 Finally, IL1 and TNF vary with sleep propensity.…”
Section: Sleep Regulatory Substance Criteriamentioning
confidence: 99%
“…Some endogenous molecules inhibit IL1 and TNF and also attenuate spontaneous NREMS including IL-4, IL-10, IL-13, 3 corticotrophin releasing hormone, 35 IL1-receptor antagonist, 4 and others (see Figure 1). We have recently found that transgenic mice with the ability to express human IL-37b, a suppressor of multiple pro-somnogenic cytokines 36 sleep less after sleep deprivation than under baseline conditions. 37 Finally, IL1 and TNF vary with sleep propensity.…”
Section: Sleep Regulatory Substance Criteriamentioning
confidence: 99%
“…Interleukin (IL)‐37 is a new member of the IL‐1 family that encompasses 11 structurally related members sharing a β‐barrel motif 7. Nevertheless, entirely distinct with most IL‐1 family members, that are characterized with proinflammatory functions, IL‐37 has emerged as an important inhibitor of the innate immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Although the existence of IL-1F7 was discovered in 2000 by in silico studies, the mediator only began to be characterized in terms of its structure, function, and biology a decade later and was subsequently named IL-37 [2]. Seminal studies clearly reported that IL-37 dampens both innate and adaptive immune responses, thus reducing general inflammation; indeed, IL-37, when present during Toll-like/IL-1 receptor stimulation or uric acid sensing, greatly reduces the synthesis of many proinflammatory cytokines [2,3].…”
Section: Discovery and Characterization Of Il-37mentioning
confidence: 99%
“…Seminal studies clearly reported that IL-37 dampens both innate and adaptive immune responses, thus reducing general inflammation; indeed, IL-37, when present during Toll-like/IL-1 receptor stimulation or uric acid sensing, greatly reduces the synthesis of many proinflammatory cytokines [2,3]. Consistent with these findings, experiments utilizing several different animal models support the concept that IL-37 is protective toward inflammatory conditions, such as endotoxic shock, myocardial infarction, metabolic syndrome, asthma, acute lung injury, and ischemic liver disease [3].…”
Section: Discovery and Characterization Of Il-37mentioning
confidence: 99%
See 1 more Smart Citation